Identification of Musculoskeletal Disorder's Complaints with the Nordic Body Map Method for the Elderly: Identifikasi Keluhan Musculoskeletal Disorder’s dengan Metode Nordic Body Map Terhadap Lansia - Bagas Anjasmara; Andi Fadhilah Tenriwulan; Auliyahur Rabbani (Universitas Muhammadiyah Sidoarjo, 2023)
Musculoskeletal disorders (MSDs) are prevalent concerns among the elderly, particularly in occupations involving prolonged repetitive activities such as fishing and farming. This observational cross-sectional study aimed to identify and assess MSD complaints among active elderly fishermen and farmers in rural communities. A total of 50 participants aged 60-65 were surveyed using the Nordic Body Map (NBM) questionnaire to analyze changes in the distribution and severity of MSDs. Results indicated that 70% of respondents were in the 60-65 age group, predominantly male (76%), with females accounting for 24% (12 individuals). The analysis revealed a substantial prevalence of severe MSD complaints (46%), primarily manifested as lower back pain (52%). These findings highlight the significant burden of MSDs among elderly agricultural workers, emphasizing the need for targeted interventions and preventive strategies to enhance their well-being and quality of life. Highlights: High Prevalence: Musculoskeletal disorders (MSDs) exhibit a high prevalence among elderly agricultural workers engaged in repetitive tasks. Severe Impact: The study reveals a substantial proportion of elderly individuals experiencing severe MSDs, particularly lower back pain. Occupational Focus: The research sheds light on the specific challenges faced by aging farmers and fishermen, emphasizing the necessity for targeted interventions and preventive measures. Keywords: Musculoskeletal disorders, Elderly, Agricultural workers, Prevalence, Severity